Effects of Perceived Parenting on Adolescent Psychological Well-being. (KYAMC Journal, 2024)
Background: Parenting has become increasingly important in the contemporary world, with an emphasis on many aspects and forms of parenting. It has a direct impact on the child's physical as well as psychological well-being and development.Objective: To determine the effects of perceived parenting on psychological well-being of late adolescents at Police Lines School and College, Rangpur, Bangladesh.Materials and Methods: A cross-sectional study was directed to determine the effects of perceived parenting on the psychological well-being of late adolescents at Police Lines School and College, Rangpur, Bangladesh. The semi-structured questionnaire was constructed to measure the psychological well-being of adolescents by ‘Ryff Scales of Psychological Well-Being’.Results: The mean age of the participants was 17.7±0.6 years and about two-thirds of them were from the age group ≥18 years (61.1%). Regarding the psychological well-being of adolescents, the mean scores of autonomy were 3.6±0.7, environmental mastery was 4.1±0.9, personal growth was 4.6±0.6, a positive relationship was 4.1±0.8, purpose in life was 4.5±1.0 and self-acceptance was 4.1±0.8. Most of the adolescents slightly agree on autonomy (49.1%), environmental mastery (43.4%), positive relationship (51.4%), self-acceptance (50.9%) and average agrees on personal growth (55.7%), purpose in life (40.6%). The mean of PWB scores was 4.2±0.5. Two-thirds of the participants (67.1%) slightly agreed about the psychological well-being of the adolescents and only 6.3% slightly disagreed. The level of psychological well-being of adolescents was statistically significant with autonomy, environmental mastery, personal growth, positive relationship, purpose in life, and self-acceptance (p